2015
DOI: 10.17051/io.2015.86261
|View full text |Cite
|
Sign up to set email alerts
|

Öğretmenlerin Örgütsel Muhalefetin Nedenlerine İlişkin Görüşleri

Abstract: ABSTRACT. The aim of this study is to find out the reasons of teachers' dissent against school administration in secondary schools. The research was in survey model. The research population consisted of teachers working in the public secondary schools located in the city center of Mardin during the 2011-2012 academic year. Randomly selected 191 teachers composed the sample. The datum of the study were collected through a questionnaire of 23 items taken from "Dissent's Reasons" section of "Scale of Organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…On the other hand, in the dimension of "lateral dissent", the teachers in big schools (M=3,61) have more dissent than those in the small (M=3,58) and medium sized schools (M=3,42). In the similar studies conducted by Dağlı and Ağalday [32,33,34] there was not found a significant difference among the perceptions of teachers according to the school size. Related researches also support the findings of this research.…”
Section: Discussionmentioning
confidence: 69%
“…On the other hand, in the dimension of "lateral dissent", the teachers in big schools (M=3,61) have more dissent than those in the small (M=3,58) and medium sized schools (M=3,42). In the similar studies conducted by Dağlı and Ağalday [32,33,34] there was not found a significant difference among the perceptions of teachers according to the school size. Related researches also support the findings of this research.…”
Section: Discussionmentioning
confidence: 69%